Exploration of Plagiarism Practices in Open and Distance Learning (ODL): Tahira Bibi,Amtul Hafeez - Exploration of Plagiarism Practices in Open and Distance Learning (ODL), (PJDOL, 2023)
Open and distance learning (ODL) system is unique, flexible, less costly and preferable mode of education across the world. Intellectual Property Rights (IPR) concept, and its related laws and procedures particularly plagiarism are new in the education system of Pakistan.